An Evaluation of Financial Technology and Financial Inclusion of SMEs Entrepreneurs in Niger State (Lapai Journal of Economics, 2024)
This study is an evaluation of financial technology and financial inclusion of SMEs entrepreneurs in Niger State. The study uses quantitative and survey research designs. A closed-ended questionnaire was used to generate primary data from 400 respondents. 355 questionnaires were retrieved for analysis and interpretations. The research uses multiple linear regression for data analysis and interpretation. The findings of the study reveal that perceived risk, agent trust, and service charges have positive and significant effect on financial inclusion of SMEs entrepreneurs in Niger State. While service trust has negative and significant effect on financial inclusion of SMEs entrepreneurs in Niger State. The study recommends that CBN, SMEDAN, and NDE should play a vital role in promoting financial inclusion among SMEs by facilitating partnerships between financial institutions and Fintech providers, providing tailored capacity-building programmes, and raising awareness among entrepreneurs about the benefits and opportunities of fintech services. More so, the study recommends that building trust between entrepreneurs and Fintech agents is crucial. Policymakers, financial institutions, and Fintech providers need to prioritize the development of trustworthy and reliable agent networks. This can be achieved through training programs for agents, ensuring transparency in transactions, and establishing strong regulatory frameworks to monitor agent conduct.